Penguatan Kesadaran Hukum Perlindungan Data Pribadi melalui Program Sosialisasi Undang-Undang Nomor 27 Tahun 2022 - Rahtami Susanti; Selamat Widodo; Widya Nirmalawati (Universitas Pahlawan Tuanku Tambusai, 2026)
The development of digital technology has led to an increase in the processing of personal data in various community activities, but this has not been matched by adequate legal awareness regarding personal data protection. This condition has the potential to cause data leaks and misuse that are detrimental to the community. This community service activity aims to strengthen legal awareness and increase public understanding of personal data protection through the dissemination of Law Number 27 of 2022 concerning Personal Data Protection. The methods used include public education through legal counseling, material presentations, and interactive discussions with partner groups. The results of the activity show an increase in public awareness of the importance of personal data protection and a better understanding of the rights of personal data subjects and the legal measures that can be taken in the event of data leaks or misuse. This activity is important as a preventive measure in building a culture of legal awareness among the public in the digital age.